Effect of Repetitive Transcranial Magnetic Stimulation on Pain Management: A Systematic Narrative Review - Yang, Seoyon; Chang, Min Cheol (Frontiers in Neurology, 2020)
Recently, clinicians have been using repetitive transcranial magnetic stimulation (rTMS) for treating various pain conditions. This systematic narrative review aimed to examine the use and efficacy of rTMS for controlling various pain conditions. A PubMed search was conducted for articles that were published until June 7, 2019 and used rTMS for pain alleviation. The key search phrase for identifying potentially relevant articles was (repetitive transcranial magnetic stimulation AND pain). The following inclusion criteria were applied for article selection: (1) patients with pain, (2) rTMS was applied for pain management, and (3) follow-up evaluations were performed after rTMS stimulation to assess the reduction in pain. Review articles were excluded. Overall, 1,030 potentially relevant articles were identified. After reading the titles and abstracts and assessing eligibility based on the full-text articles, 106 publications were finally included in our analysis. Overall, our findings suggested that rTMS is beneficial for treating neuropathic pain of various origins, such as central pain, pain from peripheral nerve disorders, fibromyalgia, and migraine. Although data on the use of rTMS for orofacial pain, including trigeminal neuralgia, phantom pain, low back pain, myofascial pain syndrome, pelvic pain, and complex regional pain syndrome, were promising, there was insufficient evidence to determine the efficacy of rTMS for treating these conditions. Therefore, further studies are needed to validate the effects of rTMS on pain relief in these conditions. Overall, this review will help guide clinicians in making informed decisions regarding whether rTMS is an appropriate option for managing various pain conditions.